Plannig sample of chemical soil properties on a conilon coffee plantation - Oliveira de Jesus Santos, Eduardo; Gontijo, Ivoney; Barreto da Silva, Marcelo (Coffee Science - ISSN 1984-3909, 2014)
Information about the spatial distribution of the soil chemical properties are of fundamental importance to the coffee plantation, as they allow making good decisions, being determinant for the crop factor. The aim of the present work was to study the spatial variability of soil chemical properties in a Conilon coffee field and to propose a methodology of soil sampling that best fits the conditions of the management system. The experiment was conducted in a crop Conilon coffee field in São Mateus, state of Espirito Santo, planted in a spacing 1.8 x 1.0 m (5,555 plants ha-1). Installed a rectangular grid of 20 x 61.6 m (1,232 m2), with 60 lines spaced with 5.6 m and 5.0 m in the row points. At each sampling point, soil samples were collected at 0.0-0.20 m deep. Statistical analysis established the adequate number of samples to analyze the studied attributes ranging from 1 to 18 points. The greatest variation was observed for Ca (CV 41.7%) and the lowest for pH (CV 6.1%). All attributes in the study showed spatial dependence structure, with strong and moderate degree. The majority of attributes evaluated were satisfactorily described by spherical model. For future sampling in similar conditions to the present study, it is suggested to collect 18 subsamples using square mesh enough to cover the entire area of interest, with sampling interval at least equal to the range of spatial dependence of the attributes studied.